The Influence of Social Support on the Psychological Well Being of Students in University of Nairobi - Ngaru, Peris Njoki; Kagema, Muriuki Kagema (International Journal of Psychology, 2017)
Purpose: To determine the factors influencing mismanagement of devolved public funds and its effects on service delivery in Nairobi County. Methodology: The research design was an explanatory research design. Findings: Results revealed that parental support was significantly associated psychological well being of the students. Results also indicate that guidance and counseling and psychological well being were positively and significantly related. The findings of this study further indicated that peer support and psychological well being are positively and significant related. Finally, the study findings indicate that religious support and psychological well being were positively and significantly related. Unique contribution to theory, practice and policy: The findings of this proposed study is significant in many respects to the undergraduates, psychologists, the university management, policy makers and the general public. The support received by the students could help to decrease their psychological problems since they feel that someone is there to help them, thus helping them to perform well in academic life. By having knowledge on how social support could help students to excel in study and cope with any psychological disturbances, much information could be derived to enhance the amount of support provided. Third, this study also hopes to contribute to the research on how to help and manage students' academic achievement. By having better understanding and knowledge about social support in relation to psychological condition of the students, it could help to design and organize proper development program to help them. Since social support is very much important to students, this study will also help family, especially parents, understand their roles in helping their children so that they can help the students to decrease their psychological problems. To policy makers, the study will provide recommendation on the innovation of new ideas of social support. The study identifies policy gaps that can be fed to policy development for the betterment of strategy implementation approaches.